THE EFFECT OF CORPORATE GOVERNANCE ON UNDERPRICING DURING THE INITIAL PUBLIC OFFERING - Natsir, Khairina; Ngadiman , Ngadiman; Pranadipta, Ruth (International Journal of Application on Economics and Business, 2024)
Initial public offering (IPO) is the main gateway for private institutions to adapt to public business and list company shares on the capital market for trading. By conducting an IPO, an institution can obtain funding from the public to pay for company expansion. One phenomenon that is often encountered by business actors conducting an IPO is an underpricing situation, namely a situation where the share price offered in the primary market is lower than the share price in the secondary market. As a manifestation of the company's obligation to use public price ranges, it is the responsibility of companies across society to manage and use public funds well, transparently and accountably, so that good corporate governance can be implemented well. The aim of this research is to analyze the influence of corporate governance on underpricing in organizations conducting IPOs on the Indonesian Capital Market for the 2017-2022 period. Corporate governance is measured through the scale of the board of commissioners, independence of the board of commissioners, management ownership and institutional share ownership. There are 305 groups providing initial public services and indexed on the IDX throughout the 2017-2022 period. Random sampling techniques are used to select samples. The analysis uses a robust linear regression evaluation method. The findings of this research show that the magnitude of the board of commissioners has no effect on underpricing, the of independence commissioners has an impact on underpricing, while management proportion ownership and institutional proportion ownership have a fairly large negative effect on underpricing.